Building Gen Z Trust Through Syariah User-Generated Content - Rhoma Iskandar; Hageem Che-Ni; Luqman Hakim (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study explores the influence of Sharia-compliant User-Generated Content on social media on Generation Z consumer trust, focusing on students at Universitas Panca Sakti Bekasi as a representation of Indonesian Gen Z. Research Methodology: The research applies a quantitative method by distributing questionnaires to ninety-seven respondents. The purpose of this study is to understand how Islamic values reflected in digital content shape trust among young Muslim consumers. Results: The analysis using multiple linear regression revealed that the intensity of interaction with Sharia UGC and the credibility of content creators had a significant positive influence on consumer trust, while content quality showed no significant effect. Altogether, these three variables contribute to explaining the dynamics of consumer trust among Gen Z. Conclusions: Sharia UGC plays a vital role in shaping trust, highlighting that industry players should prioritize engagement and credibility rather than focusing solely on content quality. Limitations: This study suggests the need for broader future studies. This research contributes to the literature by providing references for sustainable exploration in Sharia digital marketing. Contributions: This study highlights the importance of encouraging engagement and credibility in digital marketing strategies to increase Gen Z's trust in halal products in the digital era.